Bermain Gitar Untuk Keterampilan Pra Vokasional Pada Anak Tunanetra - Sri Widati, ; Deny Tri Saksono, (Pendidikan Luar Biasa, 2008)
The goals of this research increase pre vocational skill at blind children in SDLB-A YPAB Surabaya, add institute teaching material as ability of pre vocational skill for blind child and as future benefit and life of blind children in society.This research is pra experiment research which use research design is one group pre test and post test with technique analyze statistic non parametric with sign test ZH. This research use observation, interview, and test method in data collection.And the result of this research is obtained ZH value = 1,8 bigger than critical Z value 5% that is 1,64 so it refuses Ho, it can be concluded that give play guitar training  can increase pre vocational at blind children in SDLB-A YPAB Surabaya.In this research, researcher give advice for parents to guide childs interest to special skill. By increasing the skill in non formal education (course); teachers should know through childs interest early and guide as a skill; and for blind children use their skill with play guitar continuously.